Анализ и оценивание информационных рисков - Одарченко, А. С.; Дейнеко, А. А. (ХНУРЭ, 2009)
In the given report questions of methods of an estimation of information risks are discussed. Existing techniques and algorithms of an estimation of risks and also an urgency and expediency of an estimation of information risks are considered. Ordered results possible adapt in different organizations with different levels of IMS.